2017
DOI: 10.3390/molecules22081315
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Purple Sweet Potato Color on Hepatic Inflammation Is Associated with Restoration of NAD+ Levels and Attenuation of NLRP3 Inflammasome Activation in High-Fat-Diet-Treated Mice

Abstract: Purple sweet potato color (PSPC), a class of naturally occurring anthocyanins, exhibits beneficial effects on metabolic syndrome. Sustained inflammation plays a crucial role in the pathogenesis of metabolic syndrome. Here we explored the effects of PSPC on high-fat diet (HFD)-induced hepatic inflammation and the mechanisms underlying these effects. Mice were divided into four groups: Control group, HFD group, HFD + PSPC group, and PSPC group. PSPC was administered by daily oral gavage at doses of 700 mg/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 56 publications
(85 reference statements)
3
33
1
Order By: Relevance
“…An increasing body of evidence suggests that two major NAD + precursors, NR and NMN could offer therapeutic potential for metabolic disease and ageing [29]. NR supplementation in food (200-400 mg/kg, ranging from 8-18 weeks) has been shown in multiple studies with HFD fed male mice to protect against body weight gain, to improve glucose tolerance, and to reduce hepatic steatosis, [16,30], lipid accumulation, liver fibrosis [31], and hepatic ER stress [32]. Various rodent studies that used single or multiple NMN doses (range 300-500 mg/kg) have shown beneficial effects in cardiac injury [33], heart failure [34], improved brain function and memory [35], enhanced mitochondrial oxidative metabolism [36] and hepatic mitochondrial respiration [15].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence suggests that two major NAD + precursors, NR and NMN could offer therapeutic potential for metabolic disease and ageing [29]. NR supplementation in food (200-400 mg/kg, ranging from 8-18 weeks) has been shown in multiple studies with HFD fed male mice to protect against body weight gain, to improve glucose tolerance, and to reduce hepatic steatosis, [16,30], lipid accumulation, liver fibrosis [31], and hepatic ER stress [32]. Various rodent studies that used single or multiple NMN doses (range 300-500 mg/kg) have shown beneficial effects in cardiac injury [33], heart failure [34], improved brain function and memory [35], enhanced mitochondrial oxidative metabolism [36] and hepatic mitochondrial respiration [15].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the ethyl acetate fractions with the highest CQA content were associated with the highest scavenging activities towards 2,2-diphenyl-1-picrylhydrazyl (DPPH) and higher ferric ion reducing antioxidant power (FRAP)-reducing power.Foods 2020, 9, 15 2 of 14 antioxidant power (FRAP)-reducing power was almost 6.14, 3.37, and 9.43 times higher than that of the common vegetables like spinach, broccoli, and green cabbage, respectively [12]. In addition, the cellular and in vivo pharmacological evaluation of sweet potato leaf extract exhibited a wide range of health-promoting biological activities including antioxidative, anticancer, antibacterial, antidiabetic, and anti-inflammation [9,[13][14][15]. Sweet potato leaves are thus nutritional and functional foods.Currently, 95-98% of sweet potato leaves in China are discarded as waste with low value; the remaining 2-5% are mainly used for livestock [16], which leads to a huge waste of resources and creates environmental pollution problems.…”
mentioning
confidence: 99%
“…Foods 2020, 9, 15 2 of 14 antioxidant power (FRAP)-reducing power was almost 6.14, 3.37, and 9.43 times higher than that of the common vegetables like spinach, broccoli, and green cabbage, respectively [12]. In addition, the cellular and in vivo pharmacological evaluation of sweet potato leaf extract exhibited a wide range of health-promoting biological activities including antioxidative, anticancer, antibacterial, antidiabetic, and anti-inflammation [9,[13][14][15]. Sweet potato leaves are thus nutritional and functional foods.…”
mentioning
confidence: 99%
“…The regular intake of anthocyanins is also highly associated with the prevention of various chronic liver diseases, and it can reduce lipid accumulation in liver tissues and alleviate oxidative stress and hepatic inflammation [25,102,[151][152][153][154][155][156]. Other hepatoprotective effects of purple sweet potatoes include hepatic insulin resistance in high-fat diet-treated mice through the decrease of reactive oxygen species (ROS) production and the inhibition of endoplasmic reticulum (ER) liver stress (administration of purple sweet-potato color at the dose of 700 mg/kg/day) [157], through the decrease in the expression of ionized calcium-binding adapter molecule 1 (Iba1), tumor necrosis factor-α, interleukin-1β, suppressors of cytokine signaling3 (SOCS3), and galectin-3 (administration of purple sweet potato color at the dose of 500 mg/kg/day) [158], or through the inhibition of nucleotide-binding domain, leucine-rich repeat (NLR) family, pyrin domain containing 3 (NLRP3) inflammasome activation (administration of purple sweet potato color at the dose of 700 mg/kg/day) [159]. Moreover, the combinative use of black soybean and purple sweet potato (mixtures of 2:2 for black soybean and purple sweet potato) resulted in improved insulin sensitivity in streptozotocin-induced diabetic rats through the improvement of insulin and insulin receptor substrate-1 (IRS-1) expression, the increase of superoxide dismutase (SOD) levels, and reduced pancreatic necrosis [160].…”
Section: Sweet Potatomentioning
confidence: 99%